2000
DOI: 10.1128/iai.68.2.942-947.2000
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Urease-Negative Mutants of Yersinia enterocolitica Serotypes O:3 and O:8: Role of Urease in Virulence and Arthritogenicity

Abstract: Yersinia enterocolitica serotype O:3 and O:8 urease-negative mutants unable to express the 19-kDa ␤ subunit of urease were constructed and tested for virulence and arthritogenicity. Our results indicate that urease is needed for full virulence in oral infections and that it is not an arthritogenic factor in the rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…In each case, subsequent studies revealed that the in vitro production of each of these virulence factors at a high temperature required specific conditions (36,41). Other virulence factors of Y. enterocolitica are also optimally expressed at low temperatures, including urease and O-antigen outer core (2,9,16,48). A similar scenario has also been described for Vibrio cholerae, which produces much higher levels of cholera toxin in vitro at low temperatures (Ͻ30°C) than at a high temperature (37°C) (40,47).…”
Section: Discussionmentioning
confidence: 99%
“…In each case, subsequent studies revealed that the in vitro production of each of these virulence factors at a high temperature required specific conditions (36,41). Other virulence factors of Y. enterocolitica are also optimally expressed at low temperatures, including urease and O-antigen outer core (2,9,16,48). A similar scenario has also been described for Vibrio cholerae, which produces much higher levels of cholera toxin in vitro at low temperatures (Ͻ30°C) than at a high temperature (37°C) (40,47).…”
Section: Discussionmentioning
confidence: 99%
“…Because the natural host infection by Brucella frequently occurs via the oral route, the bacterium has to tolerate low pH during its passage through the digestive tract. Recent work (18) reported that urease-negative mutants of Yersinia enterocolitica were less virulent after intragastric inoculation. Moreover, a previous study of the environmental conditions that B. suis encounters in the host cell has demonstrated that this bacterium survives and remains enclosed in phagosomes which are rapidly acidified.…”
Section: Discussionmentioning
confidence: 99%
“…This factor is not essential for systemic infection, but it is necessary for the efficient invasion of the gastrointestinal tract by promoting bacterial uptake by M cells, an event that results in efficient colonization of the Peyer's patches during the earliest phases of infection (31). Urease contributes to virulence by protecting bacteria from the lethal assault of rapid acidification, a situation that Y. enterocolitica endures as it passes though the host gastric regions (16,40).…”
mentioning
confidence: 99%